Nanostructured Lipoxin A4: Understanding Its Biological Behavior and Impact on Alzheimer’s Disease (Proof of Concept) - Natália Cristina Gomes-da-Silva; Isabelle Xavier-de-Britto; Marilia Amável Gomes Soares; Natalia Mayumi Andrade Yoshihara; Derya Ilem Özdemir; Eduardo Ricci-Junior; Pierre Basílio Almeida Fechine; Luciana Magalhães Rebelo Alencar; Maria das Graças Muller de Oliveira Henriques; Thereza Christina Barja-Fidalgo; Cristian Follmer; Ralph Santos-Oliveira (Pharmaceutics)
Background/Objectives: Lipoxins, particularly Lipoxin A4 (LXA4), are endogenous lipid mediators with potent anti-inflammatory and pro-resolving properties, making them promising candidates for the treatment of inflammatory and neurodegenerative disorders. However, their therapeutic application is limited by poor stability and bioavailability. This study aimed to develop and characterize nanomicelles encapsulating LXA4 (nano-lipoxin A4) to improve its pharmacological efficacy against Alzheimer’s disease (AD), a neurodegenerative condition marked by chronic inflammation and beta-amyloid (Aβ) accumulation. Methods: Nano-lipoxin A4 was synthesized using Pluronic F-127 as a carrier and characterized in terms of morphology, physicochemical stability, and in vitro activity against Aβ fibrils. Dissociation of Aβ fibrils was assessed via Thioflavin-T fluorescence assays and transmission electron microscopy. In vivo biodistribution and pharmacokinetic profiles were evaluated using technetium-99m-labeled nano-lipoxin A4 in rodent models. Hepatic biochemical parameters were also measured to assess potential systemic effects. Results: In vitro studies demonstrated that nano-lipoxin A4 effectively dissociated Aβ fibrils at concentrations of 50 nM and 112 nM. Electron microscopy confirmed the disruption of fibrillar structures. In vivo imaging revealed predominant accumulation in the liver and spleen, consistent with reticuloendothelial system uptake. Pharmacokinetic analysis showed a prolonged half-life (63.95 h) and low clearance rate (0.001509 L/h), indicating sustained systemic presence. Biochemical assays revealed elevated liver enzyme levels, suggestive of increased hepatic metabolism or potential hepatotoxicity. Conclusions: Nano-lipoxin A4 exhibits significant therapeutic potential for Alzheimer’s disease through effective modulation of Aβ pathology and favorable pharmacokinetic characteristics. However, the elevation in liver enzymes necessitates further investigation into systemic safety to support clinical translation.